Spine surgery outcome in patients who sought compensation after a motor vehicle accident: a retrospective cohort study. Issue 1 (December 2016) - Sarrami, Pooria; Ekmejian, Rafael; Naylor, Justine; Descallar, Joseph; Chatterji, Robindro; Harris, Ian
Abstract Background Back and neck pain are common after road traffic injury and are treated by spine surgery in some cases. This study aimed to describe the outcomes of spine surgery in people who made an insurance claim after road traffic accidents without an associated spinal fracture or dislocation. Methods This study was a retrospective cohort based on insurers' data of Compulsory Third Party (CTP) claims. File audit and data extraction were undertaken using a study-specific proforma. Primary outcomes were ongoing pain and symptoms, complications, return to work and pre-injury duties, and ongoing treatment 2 years following spine surgery. Secondary outcomes were health care costs based on data provided by the insurers. Results After screening 766 files, 90 cases were included (female: 48; mean age: 46 years). Among the subjects who were working prior the injury, the rate of return to work was 37% and return to pre-injury duties was 23% 2 years following the surgery. The average number of appointments with health care professionals in the 1 year after surgery was 21, compared to 10 for the 1 year prior to surgery (p  = 0.03). At 2 years following the initial surgery, 21% of claimants had undergone revision spine surgery; 68% reported ongoing back pain and 41% had ongoing radicular symptoms. The difference between costs 1 year before and after surgery (excluding surgical costs) was statistically significant (p  = 0.04). Fusions surgery was associated with higher total costs than decompression alone. After adjusting for surgery type, lumbar surgery was associated with higher costs in the 1 year after surgery and total surgical costs compared to cervical surgery. Conclusions The majority of claimants continued having clinical symptoms, continued using health care and did not return to work despite undertaking spine surgery.